Ancient Rome : the archaeology of the eternal city - Coulston, J. C.; Dodge, Hazel (Monograph (University of Oxford. School of Archaeology), 2000)
A major new book on the archaeology of Rome. The chapters, by an impressive list of contributors, are written to be as up-to-date and useful as possible, detailing lots of new research. There are new maps for the topography and monuments of Rome, a huge research bibliography containing 1,700 titles and the volume is richly illustrated. Essential for all Roman scholars and students.